Arab Teachers' Well-Being upon School Reopening during COVID-19: Applying the Job Demands-Resources Model - Sawsan Awwad-Tabry; Inbar Levkovich; Timothy Pressley; Shiri Shinan-Altman (MDPI AG, 2023)
Once the major threat of the COVID-19 pandemic diminished, schools reopened, and teachers once again had to cope with unprecedented challenges. The impact of these challenges on the emotional well-being of Arab teachers, who have a unique set of challenges within the Israeli school educational system, has received little attention in the recent literature. In this cross-sectional study, we examined 300 Arab teachers' well-being in Israel in May 2021, three months after schools were reopened. All study hypotheses were confirmed. Findings indicate the need to promote a sense of well-being among Arab teachers in stressful conditions and to design solutions specifically tailored to support them in accordance with their cultural and social characteristics. Israel's Ministry of Education should encourage school administrators to seek ways to provide a supportive environment for Arab teachers in school environments in order to improve their performance and retention, and maintain their well-being.